2006
DOI: 10.1182/blood.v108.11.3609.3609
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of the Tyrosine Kinase Inhibitor PKC412 in Advanced Systemic Mastocytosis: Preliminary Results.

Abstract: Background: Advanced forms of systemic mastocytosis (aggressive systemic mastocytosis [ASM] and mast cell leukemia [MCL]) are myeloproliferative disorders with few treatment options and a poor prognosis. In the majority of patients (pts), the pathogenesis of ASM/MCL is related to constitutive activation of the receptor tyrosine kinase (TK) KIT, due to an aspartate to valine mutation within protein codon 816 (D816V). D816V KIT is imatinib resistant both in vitro and in vivo. We demonstrated that PKC412 (N-benzo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Accordingly, PKC412 was initially used on a compassionate basis in a case of MCL, resulting in a good partial response associated with marked improvement in the patient performance status, resolution of organ dysfunction and a dramatic decrease in both BM MC infiltration and circulating MC; however, after 3 months of therapy, progression to AML was observed (Gotlib et al , 2005). A phase II study designed to assess PKC412 efficacy and safety in ASM/MCL patients is currently in progress (Gotlib et al , 2006); preliminary results of this study showed partial (but not complete) responses in six of nine ASM cases. In order to improve the efficacy of PKC412, synergistic interactions with AMN107 therapy have been evaluated in vitro showing induction of apoptosis and downregulation of CD2 and CD63 in both HMC‐1 V 560 G , D 816 V cells and in primary neoplastic MC (Gleixner et al , 2006).…”
Section: Kit‐targeted Therapy In Mastocytosismentioning
confidence: 99%
“…Accordingly, PKC412 was initially used on a compassionate basis in a case of MCL, resulting in a good partial response associated with marked improvement in the patient performance status, resolution of organ dysfunction and a dramatic decrease in both BM MC infiltration and circulating MC; however, after 3 months of therapy, progression to AML was observed (Gotlib et al , 2005). A phase II study designed to assess PKC412 efficacy and safety in ASM/MCL patients is currently in progress (Gotlib et al , 2006); preliminary results of this study showed partial (but not complete) responses in six of nine ASM cases. In order to improve the efficacy of PKC412, synergistic interactions with AMN107 therapy have been evaluated in vitro showing induction of apoptosis and downregulation of CD2 and CD63 in both HMC‐1 V 560 G , D 816 V cells and in primary neoplastic MC (Gleixner et al , 2006).…”
Section: Kit‐targeted Therapy In Mastocytosismentioning
confidence: 99%